Establishment of Accuracy Testing Facilities for Terrestrial Laser Scanners - Davison, Wayne (Division of Geomatics, 2019)
Measurement instruments that are required for high precision and reliable work need to have regular checks to ensure they are always performing at the required level of accuracy. A Terrestrial Laser Scanner is one such instrument and with the vast amount of information that this machine is able to capture, it is especially important to run regular accuracy checks. This research is building on the work that has been done by previous researchers on the assessment of instrument accuracy and the establishment of facilities specialized for this assessment. Theoretical principles are investigated in the form of Least Squares Adjustments, similarities to panorama photography and photogrammetric accuracy. Terrestrial Laser Scanners are reviewed with respect to their scanning principles and data acquisition. The methodology incorporated in this research encompasses the positioning of targets, their survey to establish high accuracy coordinates through various methods of adjustment and thereafter the scanning of those targets. Comparisons were done using derived angles and distances between the targets to discover the point accuracy of the Laser Scanner. This was done for two facilities; a short range facility (1 to 15 meters) and a medium range facility (1 to 75 meters). The medium range facility also included a range testing baseline for distance accuracy assessments. The outcomes from the comparisons between the surveyed control data and the laser scanner observed data indicated that the laser scanner is performing below the accuracy of the surveyed data. The laser scanner was further compared against the manufacturer quoted performance specifications and revealed the laser scanner to be performing below the quoted values. The laser scanner in question showed stronger results in the horizontal measurements over the vertical measurements. All results suggested the laser scanner was delivering weak results in the vertical observations due to a mis-alignment of individual scan halves. This research was able to establish two accuracy assessment facilities specialized for Terrestrial Laser Scanners under these same conditions. Both facilities were used in conjunction, to analyze the Z+F Imager 5010C laser scanner and determine the point accuracy in terms of the observed angles and distances from this machine. The results are also able to identify errors in the performance of the laser scanner and whether or not it is performing within the manufacturer specifications by noticing any large values such as in the case of the vertical observations for this instrument.